I thought my soul would rise and fly : the diary of Patsy, a freed girl - Hansen, Joyce (New York : Scholastic, 1997)
Twelve-year-old Patsy keeps a diary of the ripe but confusing time following the end of the Civil War and the granting of freedom to former slaves.
1 2 6 7 8 11 13 15 18 19 26 27 29 33 35 36
Keywords: Afro-Americans -- Juvenile fiction; Reconstruction -- Juvenile fiction; Afro-Americans -- Fiction; Reconstruction -- Fiction; Diaries -- Fiction; African Americans -- History -- 1863-1877 -- Juvenile Fiction; United States -- History -- 1865-1898 -- Juvenile Fiction; United States -- History -- 1865-1898 -- Fiction